ANALISIS RANTAI NILAI KOMODITI KELAPA (Cocos nucifera L.) DI DISTRIK MISOOL UTARA KABUPATEN RAJA AMPAT - Ery Atmojo; Rajab Rajab (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2019)
Besides using area approach, pre-eminent product development such as coconut (Cocos nucifera L.) commodities in North Misool also need apply value chain approach. The aim of this research were to know both value chain and the strategic value of coconut product as main agriculture commodity in North Misool. Primary data collecting technique was conducted by means of structural semi interview method for man to man of respondent ar by using focus group discussion. Data type collected in this study was classified to primary and secondary data. Primary data obtained by interview to all of importance respondents and field observation, while secondary data sekunder obtained from literacy study from government agency documents and reports such as BPS, Bappeda, and other relevant references. Data collection was analysed by using the qualitative method. The result of research showed that the rate of the coconut plantation harvest in North Misool was 1,646 hectare, with coconut production reach up to 805.94 tones per year and the mean of its contribution for earnings of farmers was equal to 4.97 million rupiah per month. The value chain of coconut product was started by production, processing and copra gathering gone the round of altogether sold to interisland merchant then selling copra to Bitung. The program to increase both productivity and agribisnis of coconut was estimated can increased coconut product up to 10% per year.